The Influence of Complexity Leadership on Curriculum Innovation in Sekolah Penggerak within the DKI Jakarta Region: (Pengaruh Complexity Leadership terhadap Inovasi Kurikulum pada Sekolah Penggerak di Wilayah DKI Jakarta) - Hasyim Asyari; Taufiqurrahman (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2026)
"This study aims to analyze the influence of Complexity Leadership on curriculum innovation in Activator Schools (Sekolah Penggerak) within the DKI Jakarta region. The relevance of Complexity Leadership Theory (CLT) in Jakarta is underscored by the frequent stagnation of traditional top-down leadership models in addressing the complexities of the Merdeka Curriculum within heterogeneous urban environments. A quantitative approach with an explanatory correlational design was applied to a sample of 301 senior high school teachers selected through proportional random sampling. Data was analyzed using variance-based Structural Equation Modeling (SEM) via WarpPLS software. The results indicate that Complexity Leadership comprising administrative, adaptive, and enabling functions exerts a positive and significant influence on curriculum innovation. The enabling leadership dimension was found to be the most dominant factor in facilitating "adaptive space" for teachers to creatively implement the Merdeka Curriculum (β = 0.428, p < 0.001). These findings underscore the importance of shifting leadership paradigms from bureaucratic control toward network facilitation to navigate educational transformation in the capital city. This study recommends enhancing agility competencies for school principals to ensure the sustainability of adaptive and inclusive educational innovation.